Implementation of proxmox server monitoring system with laravel and vue.js - Ariel Thymoti Irmawan; Raymond Maulany (Jurnal Mantik, 2024)
Large organizations now heavily rely on Information Technology and Telecommunications (ICT) for their operations. Server availability is crucial in managing data centers and applications, but the increase in physical servers often involves high costs. Therefore, virtualization technology has emerged as an efficient solution. The research aims to develop the "Proxmox Server Monitoring System" to automatically monitor the availability and performance of Proxmox VE servers with real-time notifications in case of failures, enhancing efficiency and availability. This research is expected to improve the utilization of Proxmox VE server resources, provide automated monitoring, detect failures faster, and reduce downtime, thereby better supporting organizational operations. The potential contribution of this research lies in optimizing server resource usage with virtualization technology, improving server infrastructure efficiency and availability, and reducing the risk of failures and downtime